Penilaian Atribut Usabilitas oleh Gamer First Person Shooter (FPS) Indonesia - Paulina K. Ariningsih; Yun P. Mulyani; Kristianto A. Nugroho; Chandra S. Rahardjo (Jurnal Rekayasa Sistem Industri, 2016)
Computer games, especially First Person Shooter (FPS) have become one of the fastest growing and most economically sucessful software in Indonesia. Given the potential economic benefits of the FPS games, it is important to design its user interface as usable as possible to win the market. In accordance, it is crucial to find out what user interface factors should be considered in designing an FPS game. These factors can be used as a designing guide for game developers in Indonesia. The purpose of this paper is to discover the main user interface factors that should be considered in designing an FPS game especially from usability point of view and to suggest improvement of the user interface in current FPS game.Fourty (40) usabilty attributes from literature review are qualitatively grouped into 5 factors. Those factors are: Basic FPS Feature (BFF), Basic Game Feature (BGF), Display & Sounds (D&S), Help & Hints (H&H), and Enjoyment (E). Usability testing on the factors is conducted in three different groups of players: Novice, Experienced, and Expert. Mann-Withney Test are conducted to understand performance difference for each group. The result shows that BGF and H&H are not significantly difference for all groups. While for BFF, the novice group tend to have different preference rather than other groups since there is not enough time duration given on novice users accessing the FPS feature. For D&S, expert tend to have different preference rather than other groups. Some future research potentials are also proposed in this paper.